2020
DOI: 10.3889/oamjms.2020.4528
|View full text |Cite
|
Sign up to set email alerts
|

Pancreoprotective Effect of Jicama (Pachyrhizus erosus, Fabaceae) Fiber against High-Sugar Diet in Mice

Abstract: AIM: Jicama (Pachyrhizus erosus, Fabaceae) has been promoted as a potent tuberous plant exerting both preventive and therapeutic effects against many diseases. In this present study, we aimed to investigate the pancreoprotective effect of isolated jicama fiber (JF) against glucotoxicity caused by high-sugar diet (HSD). METHODS: We performed an animal experimental research using adult male BALB/c mice with a completely randomized design consisted of four treatments and six replications. The treatments wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Soluble fibre causes a slower gastric emptying rate and increases the viscosity of digested food in the intestine, thereby reducing glucose absorption. As a result, the amount of glucose that reaches the portal vein is lower (Santoso et al, 2020). In addition, fibre can also be fermented by intestinal microbes to produce short-chain fatty acids, including acetate, butyrate, and propionate.…”
Section: Pancreas Histologymentioning
confidence: 99%
“…Soluble fibre causes a slower gastric emptying rate and increases the viscosity of digested food in the intestine, thereby reducing glucose absorption. As a result, the amount of glucose that reaches the portal vein is lower (Santoso et al, 2020). In addition, fibre can also be fermented by intestinal microbes to produce short-chain fatty acids, including acetate, butyrate, and propionate.…”
Section: Pancreas Histologymentioning
confidence: 99%
“…A study on male Bagg and Albino (BALB/c) mice with a treatment of tuber fibers resulted in a significant reduction in blood glucose levels [ 62 ]. In a recent study, the pancreatic tissue was also found to be protected from high fat diet-induced islet hyperplasia and hypertrophy in BALB mice treated with tuber powder [ 63 , 64 ]. Probiotic yogurt made from the P. erosus tuber was also found to be effective in decreasing blood glucose in DDY strain mice when compared with normal probiotic yogurt [ 65 ].…”
Section: Bioactivities (In Vitro and In Vivo)mentioning
confidence: 99%
“…Jicama, or yam bean (Pachyrhizus erosus (L.) Urban), is a widely produced crop in Indonesia (Santoso et al, 2020). It can be integrated into marginal farming systems in drought-prone locations, such as Sub-Saharan Africa (Buckman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%